Facebook: An Effective WEB 2.0 Technology for Blended EFL Classrooms in Indonesia - Husnawadi Husnawadi; Nanang Sugianto (EDULANGUE, 2018)
The 21st century learning has been a landmark in the use of digital technologies that serve pedagogical purposes, which includes the proliferating use of blended learning (Henceforth BL). A mixture of face-to-face (FTF) and online learning (Internet Synchronous and Asynchronous media), BL strategy has gained its popularity in the sphere of English language teaching (Hereafter ELT) due to its effectiveness in promoting learners’ language proficiency. However, the discussion on the extent to which e-learning mode plays role in English as a foreign language (Henceforth EFL) classrooms, particularly Indonesia, remains scantily documented; and a query on what can be an effective and efficient medium of e-learning in the strategy remains persistent in the foreignlanguage context. With its popularity and preferred medium of communication among teenagers across the globe, especially Indonesia, Facebook (hereafter FB) can be an answer to such a question. Hence, drawing on the Indonesian ELT context, this paper discusses the nature of BL; argues why FB can be aneffective and efficient add-on to e-learning mode in the Blended ELT context; and presents an example of its application as applied in one of the authors’ English-speaking classroom at a State University for Islamic Studies (UIN Mataram) and a reflection as the lecturer. This paper is expected to inform the English teaching practitioners or teachers on how to use social media, particularly FB, to enhance the students’ learning and learning outcomes particularly in Indonesian adult English classrooms.